Astaxanthin Production by the Red Yeast (Phaffia rhodozyma), Grown on Yeast Extract Addes Coconut Water - K H Timotius; Ana W Purnomo; V I Meitiniarti (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2003)
This experiment was conducted to evaluated the effect of yeast extract addition in fresh green coconut water medium during the batch growth and astaxanthin production of Phaffia rhodozyma MUCL 31142. The addition of yeast extract (0,025% and 0,075%) could increase the cell growth (37,12 g/l and 49,18 g/l), growth rate (0,061/hour and 0,074/hour), total production of astaxanthin (4,871 mg/l and 9,442 mg/l), specific concentration of astaxanthin (118,99 Ã‚Âµg/g biomass), production rate of astaxanthin (0,042/hour and 0,088/hour), astaxanthin yield (0,236 mg/g glucose and 0,342 mg/g glucose, and glocose consumption (19,84 g/l and 26,95 g/l). Key Word : Astaxanthin, Phaffia rhodozyma, coconut water.